Skin reaction to capsaicin in patients with Systemic Lupus Erythematosus compared to that in healthy controls - Maryam Sahebari; Javad Salimi; Peyman Shalchian Tabrizi; Mina Khodabandeh; Nazila Ariaee Nasab; Masoumeh Salari (Babol University of Medical Sciences, 2021)
Background: The interaction between nervous and immune systems has been under investigation. Transient receptor potential vanilloid type 1(TRPV1) is a ligand gated calcium channel expressed by sensory neurons which mediates neurogenic inflammatory response. Substance p which can be released following exposure to capsaicin is a TRPV1 inducer, shown to have altered concentration and function in mice with systemic lupus erythematosus (SLE). We evaluated skin reaction to capsaicin in newly diagnosed and established SLE patients compared to healthy controls. Methods: Twenty-nine SLE patients (12 newly diagnosed cases under treatment, and 17 established ones, not receiving medications) who referred to rheumatologic disease research center, and 33 healthy subjects of the control group were recruited in this study. A topical solution of capsaicin (0.075%) was applied on the volar forearm during skin test, and time to the tingling sensation, area of induration and area of redness (centimeters2) were recorded after 5, 10, and 20 minutes. Results: The area of redness and area of induration within 15 minutes, time to the tingling sensation (P=0.02), and the overall frequency of tingling sensation (P=0.01) after capsaicin skin test was considerably higher in SLE patients than the healthy controls. Redness, induration and tingling sensation were more frequent but not statistically significant among the established SLE group compared to the newly diagnosed patients. Conclusion: Since skin reaction to capsaicin is more prominent in SLE patients than the healthy individuals, neurogenic inflammation and the role of P substance should be investigated more in ongoing lupus. Capsaicin test can not predict lupus activity.